Urgensi dan Mekanisme Pengembalian Aset Hasil Tindak Pidana Korupsi - Farel, Muhammad Ronald; Ansari, Teuku Syahrul (Jurnal Ilmiah Wahana Pendidikan, 2024)
The basic idea behind asset recovery is that corrupt governments use a variety of criminal and civil procedures to strip corrupt individuals of their rights to the assets that they have amassed via corruption. Criminal and civil procedures are used to recover assets that have been confiscated in accordance with the Anti-Corruption Act. Indonesia ratified the convention into Law Number 7 of 2006, giving rise to an obligation to harmonize it with national law or implement it into a new law.